Online Learning Model in Improving Civic Responsibility as a Solution during Covid-19 Pandemic in Indonesia - Yayuk Hidayah; Meiwatizal Trihastuti; Bali Widodo (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aimed to examine the implementation of quarantine in terms of the online learning model in improving civic responsibility as a solution during the Covid-19 pandemic in Indonesia. This study's subject was 47 students (17 males and 30 females) at the Department of Teacher and Primary Education Universitas Ahmad Dahlan, Yogyakarta, which was processing Citizenship Education in the academic year 2019/2020. The researchers collected the data from students and lecturers through observation, interviews, and documentation study. The technique of data analysis was performed through descriptive qualitative analysis. The study results indicated that the online learning model at the Department of Teacher and Primary Education Ahmad Dahlan University in 2019/2020 could improve students' civic responsibility. The data have shown that civic responsibility consisted of 97 % social participation, 76 % social advocacy, and 79 % citizenship participation. This study could finally conclude that online learning model could improve civic responsibility as a solution during the Covid-19 pandemic in Indonesia and tended to be an alternative and effective model in rare situations. This research can be used as input in increasing civic responsibility as a solution during a pandemic in Indonesia.